2018
DOI: 10.1016/j.jsxm.2018.04.642
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Plaque Excision and Grafting and Supplemental Tunica Albuginea Plication for Treatment of Peyronie's Disease With Severe Compound Curvature

Abstract: Background There are limited data in the literature that describe the management of Peyronie's disease (PD) with severe compound curvature, which often requires additional straightening procedures after plaque excision and grafting (PEG) to achieve functional penile straightening (<20 degrees). Aim This study highlights the clinical distinction and our experience with men with PD and severe compound curvature treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Again, penile recurvature and shortening, as well as vasculogenic ED, were all attributed to graft contracture/scarring. A very recent study from the same working team (Table 3) demonstrated, in line with our findings, that the addition of plication stitches to plaque excision and Tutoplast grafting in men with severe compound curvature provided similar results to plaque excision and grafting alone 19 …”
Section: Discussionsupporting
confidence: 90%
“…Again, penile recurvature and shortening, as well as vasculogenic ED, were all attributed to graft contracture/scarring. A very recent study from the same working team (Table 3) demonstrated, in line with our findings, that the addition of plication stitches to plaque excision and Tutoplast grafting in men with severe compound curvature provided similar results to plaque excision and grafting alone 19 …”
Section: Discussionsupporting
confidence: 90%
“…The complimentary plication was needed for the bi‐planar nature of curvature in fifteen patients (34%). In similar studies, the combined approach rate and percentage of bi‐planar patients in this group were reported as 67% and 33% (Chow et al., 2018). Although the ratio of patients who needed additional plication was higher in the recurrence group (33.7% vs. 45%), it was not statistically significant.…”
Section: Discussionmentioning
confidence: 66%
“… 18 19 20 21 Tutoplast resulted in added penile length ranging from 0.2 cm to 0.7 cm. 22 23 24 25 SIS had an overall mean added length of 0.6 cm, with self-reported penile shortening ranging from 5% to 65%. 26 27 28 29 BMG resulted in the highest overall added penile length of 1.6 cm to 2.4 cm and low level of penile shortening ranging from 0 to 15.4%.…”
Section: Resultsmentioning
confidence: 99%